How Companies Manage Risk in the Supply Chain Through an ESG Approach? - Purwanti, Ari; Utami, Eva Yuniarti (West Science Accounting and Finance, 2025)
This study explores how companies manage risks in their supply chains through the integration of Environmental, Social, and Governance (ESG) principles. Using a systematic literature review of 10 SCOPUS-indexed journal articles, the research identifies key ESG practices and their roles in mitigating environmental, social, and governance-related risks. The findings show that ESG-driven supply chain management enhances organizational resilience, reduces vulnerabilities, and builds stakeholder trust. Environmental risks are addressed through sustainable sourcing and green logistics; social risks are mitigated via ethical labor practices, supplier audits, and community engagement; and governance risks are managed through transparency, compliance frameworks, and technological solutions such as blockchain. However, implementation challenges remain, including inconsistent ESG standards, limited supplier visibility, and resource constraints, particularly for SMEs. The review concludes that while ESG integration is still evolving, it serves as a strategic tool for sustainable and resilient supply chain management in a globally uncertain environment.